Braiding of Majorana bound states in a driven-dissipative Majorana box setup - Kunmin Wu; Sadeq S Kadijani; Thomas L Schmidt (New Journal of Physics)
We investigate a system of Majorana box qubits, where each of the Coulomb blockaded boxes is driven by an applied AC voltage and is embedded in a dissipative environment. The AC voltage is applied between a pair of quantum dots, each of which is coupled by tunneling to a Majorana box qubit. Moreover, the dissipation is created by the coupling to an electromagnetic environment. Recent work has shown that in this case the Majorana bound states (MBSs) which form the computational basis can emerge as dark states, which are stabilized by the dissipation. In our work, we show that the same platform can be used to enable topological braiding of these dissipative MBSs. We show that coupling three such Majorana boxes allows a braiding transformation by changing the tunnel amplitudes adiabatically in time.